Regulating knowledge monopolies: The case of the IPCC - Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2010)
The Intergovernmental Panel on Climate Change has a monopoly on the provision of climate policy advice at the international level and a strong market position in national policy advice. This may have been the intention of the founders of the IPCC. I argue that the IPCC has a natural monopoly, as a new entrant would have to invest time and effort over a longer period to perhaps match the reputation, trust, goodwill, and network of the IPCC. The IPCC is a not-for-profit organization, and it is run by nominal volunteers; it therefore cannot engage in the price-gouging that is typical of monopolies. However, the IPCC has certainly taken up tasks outside its mandate; the IPCC has been accused of haughtiness; innovation is slow; quality may have declined; and the IPCC may have used its power to hinder competitors. There are all things that monopolies tend to do, against the public interest. The IPCC would perform better if it were regulated by an independent body which audits the IPCC procedures and assesses its performance; if outside organizations would be allowed to bid for the production of reports and the provision of services under the IPCC brand; and if policy makers would encourage potential competitors to the IPCC.
Keywords: 330; climate change; IPCC; natural monopoly; regulation; policy advice; Klimaveränderung; Umweltorganisation; Monopol; Umweltpolitik; Welt